Catalytic Enantioselective Synthesis of Lactams through Formal [4+2] Cycloaddition of Imines with Homophthalic Anhydride. (27th January 2017) - Jarvis, Claire L.; Hirschi, Jennifer S.; Vetticatt, Mathew J.; Seidel, Daniel
Abstract: An amide‐thiourea compound, operating through a novel ion pairing mechanism, is an efficient organocatalyst for the asymmetric reaction of homophthalic anhydride with imines. N ‐aryl and N ‐alkyl imines readily undergo formal [4+2] cycloaddition to provide lactams with high levels of enantio‐ and diastereoselectivity. The nature of the key chiral ion pair intermediate was elucidated by DFT calculations.